Environmental and seasonal correlates of capercaillie movement traits in a Swedish wind farm. Issue 17 (5th August 2021) - Kämmerle, Jim‐Lino; Taubmann, Julia; Andrén, Henrik; Fiedler, Wolfgang; Coppes, Joy
Abstract: Animals continuously interact with their environment through behavioral decisions, rendering the appropriate choice of movement speed and directionality an important phenotypic trait. Anthropogenic activities may alter animal behavior, including movement. A detailed understanding of movement decisions is therefore of great relevance for science and conservation alike. The study of movement decisions in relation to environmental and seasonal cues requires continuous observation of movement behavior, recently made possible by high‐resolution telemetry. We studied movement traits of 13 capercaillie ( Tetrao urogallus ), a mainly ground‐moving forest bird species of conservation interest, over two summer seasons in a Swedish windfarm using high‐resolution GPS tracking data (5‐min sampling interval). We filtered and removed unreliable movement steps using accelerometer data and step characteristics. We explored variation in movement speed and directionality in relation to environmental and seasonal covariates using generalized additive mixed models (GAMMs). We found evidence for clear daily and seasonal variation in speed and directionality of movement that reflected behavioral adjustments to biological and environmental seasonality. Capercaillie moved slower when more turbines were visible and faster close to turbine access roads. Movement speed and directionality were highest on open bogs, lowest on recent clear‐cuts (<5 y.o.), and intermediate in all types of forest. Our results provide novel insights into the seasonal and environmental correlates of capercaillie movement patterns and supplement previous behavioral observations on lekking behavior and wind turbine avoidance with a more mechanistic understanding. Abstract : We analyzed movement traits (speed and directionality) of capercaillie, a mainly ground‐dwelling forest bird, in a Swedish wind farm. We found evidence for clear daily and seasonal variation in movement traits that reflected behavioral adjustments to biological and environmental seasonality. Capercaillie movement behavior was also related to wind turbine effects, mainly turbine visibility, and habitat characteristics.